Reprogramming of root epidermal cells in response to nutrient deficiency. (22nd January 2007) - Perry, P.; Linke, B.; Schmidt, W.
Abstract : Post-embryonic development of the root system is highly plastic to environmental cues, compensating for the sessile lifestyle of plants. The fate of epidermal cells of Arabidopsis roots is particularly responsive to nutritional signals, leading to an increase in the root's surface area in the absence of the essential but immobile minerals iron, phosphate and manganese. The resulting phenotype is characteristic of the respective condition. Growth under nutrient starvation affects the expression of genes involved in cell specification, indicating that environmental signals are perceived at an early stage of cell development. Cell fate decisions are controlled at different levels, probably integrated at the level of chromatin organization.